Do People Buy Because They Are Afraid of Missing Out? A Case Study of Jalan Flamboyan Manado - Ni kadek Meivi Jayanti; Abraham Leslie Petir Lelengboto (PT FORMOSA CENDEKIA GLOBAL, 2025)
The increasing popularity of Jalan Flamboyan as a culinary destination in Manado City is largely driven by social media promotions, particularly through user-generated reviews that influence consumer behavior. This study aims to examine the impact of Electronic Word of Mouth (E-WOM) on Purchase Intention, with Fear of Missing Out (FOMO) acting as a mediating variable. Employing a quantitative research design, data were collected from 180 respondents using structured questionnaires and analyzed through Partial Least Squares Structural Equation Modeling (PLS-SEM). The findings indicate that E-WOM significantly influences FOMO (path coefficient = 0.29) and directly affects Purchase Intention (path coefficient = 0.68). Furthermore, FOMO has a significant direct impact on Purchase Intention (path coefficient = 0.331) and serves as a complementary mediator in the relationship between E-WOM and Purchase Intention. The results suggest that online reviews not only shape consumer perceptions but also trigger emotional responses such as FOMO, which in turn enhance purchase intentions. These insights highlight the strategic importance of leveraging E-WOM and urgency-based marketing approaches to effectively drive consumer engagement and conversion.